Facilitative leadership in security services: Factor for more efficient management in crisis situation - Aleksandar Dashtevski; Jane Dukovski; Gorjan Grncharovski (UTMS Journal of Economics, 2019)
Every society should take care through the development of its security systems, to raise the level of security in the country and to guarantee the full security of its citizens. It involves protecting the constitutional legal order, sustainable economic system, cultural values, and many other issues. The security services are instruments of the state through which the basic state obligations are fulfilled, which protects the constitutional order, protection of the life and property of the citizens, the economic and political system of the state, and so on. In order to achieve that, there should be a capacity for effective leadership. Capacity building for leadership is self-awareness, developing skills and building a sense of personal commitment, and leaders are not only obliged to control resources, but they also must facilitate the work of others and involve them in the processes of change and constant improvement. The facilitator should have a vision and the result of that vision should lead to a high motivation of the team with which it operates. Such motivation leads to better results at a crucial moment.
Keywords: J53; 330; society; protection; skills; facilitator; commitment